Learning Trajectory for Learning Multiplication Rules with Islamic Values using Realistic Mathematics Education Approach - Yoga Dwi Windy Kusuma Ningtyas; Chusnul Khotimah Galatea; Naufal Ishartono; Naufal Husein Adikalan (Vygotsky: Jurnal Pendidikan Matematika dan Matematika, 2023)
This paper aims to investigate how a learning trajectory (LT) of multiplication rules support students in developing their understanding and reasoning skills. The learning activities in LT are developed by using Realistic Mathematics Education approach with Islamic values embedded. This study employed design research, which involved a cyclical process of preliminary design, experimental design, and retrospective analysis. The data were collected from 30 tenth-grade students an Islamic senior high school in Jember, Indonesia. The data collected from literature reviews, observations, interviews, videotaping, and tests. The results depicted that the LT of multiplication rules based realistic-Islamic context can support students’ thinking and reasoning about the concepts of multiplication rules. Most notably, the Islamic content and context may teach good deeds and principles that may be applied to students’ daily life.